PENGARUH MODEL PEMBELAJARAN CORE TERHADAP KEMAMPUAN BERPIKIR KRITIS DAN DISPOSISI MATEMATIS DITINJAU DARI KEMAMPUAN AWAL MATEMATIKA SISWA SMA NEGERI DI JAKARTA TIMUR - Nur Asma Riani Siregar; Pinta Deniyanti; Lukman El Hakim (JPPM (Jurnal Penelitian dan Pembelajaran Matematika), 2018)
ABSTRACTThe study aims to see the effect of CORE instruction methods toward mathematical critical thinking  ability and mathematical dispositions of high school students in East Jakarta. Samples of this research is 88 students 11th grade Science Major from SMA Negeri Jakarta Timur. Research methods is quasi experiment using treatment by level  design. Data collection were using instruments of test and questionnarie test: mathematics prior knowledge and mathematical critical thinking ability test, and mathematical dispositions questionnaire test. Data analaysis is using two way ANOVA. Results indicated that: (1) Mathematical critical thinking ability and mathematical dispositions of students treated by CORE instruction is higher than students treated by Direct Instruction, (2) There is an interaction between learning models and mathematics prior knowledge (KAM) that have significant effect toward mathematical critical thinking ability and students mathematical dispositions, (3) Mathematical critical thinking ability and mathematical dispositions of students with high KAM treated by CORE instruction is higher than students with high KAM treated by Direct Instruction, (4) There is no significant effect of learning models toward mathematical critical thinking ability and mathematical dispositions of students with low KAM.Keywords: CORE Instruction, Mathematical Critical Thinking Ability, Mathematical Dispositions, Mathematics Prior Knowledge